2002
DOI: 10.1128/jvi.76.11.5315-5325.2002
|View full text |Cite
|
Sign up to set email alerts
|

Envelope Glycoprotein Incorporation, Not Shedding of Surface Envelope Glycoprotein (gp120/SU), Is the Primary Determinant of SU Content of Purified Human Immunodeficiency Virus Type 1 and Simian Immunodeficiency Virus

Abstract: Human immunodeficiency virus type 1 (HIV-1) and simian immunodeficiency virus (SIV) particles typically contain small amounts of the surface envelope protein (SU), and this is widely believed to be due to shedding of SU from mature virions. We purified proteins from HIV-1 and SIV isolates using procedures which allow quantitative measurements of viral protein content and determination of the ratios of gag-and env-encoded proteins in virions. All of the HIV-1 and most of the SIV isolates examined contained low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
248
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(277 citation statements)
references
References 55 publications
29
248
0
Order By: Relevance
“…In the main, HIV is thought to assemble at the plasma membrane of T-cells. The finding that endocytosis signals function to maintain low levels of Env on the cell surface may explain why HIV particles collected from cultured T-cell lines have relatively low Env levels (average 7-10 spikes/virion; Chertova et al, 2002;Zhu et al, 2003). In addition, the levels of Env expression on the cell surface and on virions could be a determinant for host humoral immune responses and viral evasion (Yuste et al, 2004(Yuste et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the main, HIV is thought to assemble at the plasma membrane of T-cells. The finding that endocytosis signals function to maintain low levels of Env on the cell surface may explain why HIV particles collected from cultured T-cell lines have relatively low Env levels (average 7-10 spikes/virion; Chertova et al, 2002;Zhu et al, 2003). In addition, the levels of Env expression on the cell surface and on virions could be a determinant for host humoral immune responses and viral evasion (Yuste et al, 2004(Yuste et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…For these particles to be infectious, Env must be transported to the cell surface, but the level to which it is incorporated into budding virions is unclear. Recent data have suggested that fewer than 10 Env protein complexes (trimers) are incorporated per virion (Chertova et al, 2002;Zhu et al, 2003), and early studies of HIV infected T-cells showed that much of the newly synthesized Env is transported to lysosomes and degraded (Willey et al, 1988). However, it has recently become evident that in macrophages the assembly of Envcontaining infectious HIV occurs on intracellular membranes, that have some characteristics in common with late endosomes (Raposo et al, 2002;Pelchen-Matthews et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We used AT-2 HIV-1 viral preparations at a concentration of 3 g/ml Gag p24 Ag, which corresponds to an estimated gp120 concentration of 2 nM, given a Gag to gp120 ratio of ϳ60 (62). These data suggest that virion-associated gp120 can signal in the nanomolar range.…”
Section: Discussionmentioning
confidence: 99%
“…The number of gp120/gp41 trimers per virion ranges between 10 and 100 depending on the isolate (10). HIV gp120 is ϳ50% carbohydrate and is one of the most glycosylated proteins known (11).…”
Section: The Virus and Its Targetmentioning
confidence: 99%